M-polar Q-hesitant Anti-fuzzy Set in BCK/BCI-algebras (European Journal of Pure and Applied Mathematics, 2024)
The main objective of this paper is to effectively define a new concept of the fabulous fuzzy set theory that is called m-polar Q-hesitant anti-fuzzy set and apply it to the BCK/BCI-algebras. The m-polar Q-hesitant anti-fuzzy set is an astonishing development of the combination between the m-polar fuzzy set and the Q-hesitant fuzzy set. However, we introduce knowledge of the m-polar Q-hesitant anti-fuzzy subalgebra, m-polar Q-hesitant anti-fuzzy ideal, closed m-polar Q-hesitant anti-fuzzy ideal, m-polar Q hesitant anti-fuzzy commutative ideal, m-polar Q-hesitant anti-fuzzy implicative ideal, and m-polar Q-hesitant anti-fuzzy positive implicative of BCK/BCI- algebras. In addition, we investigate several theorems, examples, and properties of these notions.
Keywords: $φ_j$ polar decomposition; )-fuzzy subalgebra